1997
DOI: 10.1002/(sici)1097-0215(19971104)73:3<362::aid-ijc10>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for high methoxymorpholino doxorubicin cytotoxicity in doxorubicin‐resistant tumor cell lines

Abstract: Methoxymorpholino doxorubicin (MMRDX) is an anthracy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Morpholino-derivatives of DOX or DNR share common features like circumvention of multidrug resistance-related protein (MRP)-1-mediated resistance (Bakker et al, 1997), gain of activity after metabolization by CYP3A isoform(s) of cytochrome P 450 (Lewis et al, 1992), and reduced cardiotoxicity in animal models in face of sustained oxyradical generation (Sato et al, 1991). This latter finding either offers one more argument against the involvement of ROS in anthracyclineinduced chronic cardiotoxicity or suggests that ROS are formed at cellular sites that are not critical to the development of cardiac dysfunction (Sato et al, 1991).…”
mentioning
confidence: 99%
“…Morpholino-derivatives of DOX or DNR share common features like circumvention of multidrug resistance-related protein (MRP)-1-mediated resistance (Bakker et al, 1997), gain of activity after metabolization by CYP3A isoform(s) of cytochrome P 450 (Lewis et al, 1992), and reduced cardiotoxicity in animal models in face of sustained oxyradical generation (Sato et al, 1991). This latter finding either offers one more argument against the involvement of ROS in anthracyclineinduced chronic cardiotoxicity or suggests that ROS are formed at cellular sites that are not critical to the development of cardiac dysfunction (Sato et al, 1991).…”
mentioning
confidence: 99%
“…MCF7-ADR cells are cross-resistant to many other structurally distinct drugs, which are also substrates for P-glycoprotein (P-gp) and are efficiently pumped out of the cells. Previous reports indicate that MMDX is active against cultured tumor cell lines that overexpress P-glycoprotein and are highly resistant to doxorubicin; however, some crossresistance to MMDX is apparent (Kuhl et al, 1993;van der Graaf et al, 1995;Bakker et al, 1997). In contrast, in vivo studies indicate that MMDX retains substantial activity against doxorubicin-resistant tumor cells (Ripamonti et al, IC 50 values and potentiation ratios derived from these data are shown in Table 2.…”
Section: Cytotoxicity Of MMDX Activated By Rat and Humanmentioning
confidence: 95%
“…MMDX contains a methoxymorpholinyl group at the 3Ј position of the sugar moiety and is highly lipophilic. Unlike doxorubicin, MMDX is not cardiotoxic at optimal antitumor doses (Danesi et al, 1993) and shows substantially reduced cross-resistance in tumor cell lines highly resistant to doxorubicin (Ripamonti et al, 1992;Kuhl et al, 1993;van der Graaf et al, 1995;Bakker et al, 1997). MMDX toxicity is associated with induction of DNA strand breaks primarily through topoisomerase I cleavage, whereas doxorubicin induces DNA lesions through topoisomerase II cleavage (Duran et al, 1996).…”
mentioning
confidence: 99%
“…This activity is derived from DNA intercalation, mono-alkylation and inhibition of topo IIα without inter-strand DNA cross-linking [13,15]. Furthermore, unlike a classical topo IIα inhibitor such as doxorubicin, alchemix is neither a substrate for P-gp [15,23] nor significantly affected by the lower levels of topo IIα present in resistant A2780/adr cells [24]. This study examined the nature of DNA binding by alchemix and subsequent cellular pharmacology.…”
Section: Repair Of Dna Adducts In Cho Cell Linesmentioning
confidence: 99%